Natural product biosyntheses in cyanobacteria: A treasure trove of unique enzymes - Kehr, Jan-Christoph; Gatte Picchi, Douglas; Dittmann, Elke (Beilstein Journal of Organic Chemistry, 2011)
Cyanobacteria are prolific producers of natural products. Investigations into the biochemistry responsible for the formation of these compounds have revealed fascinating mechanisms that are not, or only rarely, found in other microorganisms. In this article, we survey the biosynthetic pathways of cyanobacteria isolated from freshwater, marine and terrestrial habitats. We especially emphasize modular nonribosomal peptide synthetase (NRPS) and polyketide synthase (PKS) pathways and highlight the unique enzyme mechanisms that were elucidated or can be anticipated for the individual products. We further include ribosomal natural products and UV-absorbing pigments from cyanobacteria. Mechanistic insights obtained from the biochemical studies of cyanobacterial pathways can inspire the development of concepts for the design of bioactive compounds by synthetic-biology approaches in the future.
Keywords: cyanobacteria; natural products; NRPS; PKS; ribosomal peptides